Defining the future of occupational therapy: A concept analysis of leadership development - Tracey E. Recigno; Jewel Shepherd; Paula Kramer; Jessica McHugh Conlin (Scandinavian Journal of Occupational Therapy)
Background In occupational therapy, leadership development is a fundamental skill and social process needed to advance the profession. However, there is scant literature on leadership development. Further examination of leadership development in the occupational therapy literature may provide helpful insights and strengthen the opportunity to study this concept and its efficacy.Aims/Objectives The focus of this concept analysis was to conduct a review of the historical and contemporary occupational therapy literature to evaluate how the profession distinguishes the concept of leadership development.Material and Method A principle-based concept analysis provides holistic perspectives of a concept by examining its historical and linguistic foundations.Results Dialogue about leadership development was primarily situated in grey literature with few articles found in empirical-focused, peer-reviewed journals. The analysis revealed that leadership development was understood as both a process and an outcome and was intended to support the promotion of the profession.Conclusion Despite using similar language to describe the concept, the literature did not yield one cohesive definition of leadership development.Significance A definition was proposed that integrated the various perspectives to support future empirical research around a centralized understanding of the concept of leadership development.